The study of lay theories: An important piece of the puzzle for understanding prejudice (2013)
“Lay” theories are the theories that people use in their everyday life. They not only serve people's epistemic needs to understand and make predictions about their social world but also serve their social needs to form and maintain relationships as well as psychological needs to feel in control and good about themselves. Decades of findings from cognitive, cultural, developmental, and social psychological research involving children, adolescents, and adults across numerous cultures indicate that lay theories are powerful predictors of greater or weaker prejudice, stereotyping, and discrimination toward numerous groups (gay men, overweight persons, people living with AIDS, poor persons, socially stigmatized racial/ethnic groups, women). This chapter examines how lay theories foster prejudice or tolerance toward social groups. It highlights some relevant findings on a prominent lay theory, the Protestant work ethic (PWE), which appears to have at least two intergroup implications: one for prejudice and one for tolerance. The tolerant implication of PWE seems to exist across age, cultural, and social status groups; whereas the intolerant implication seems to be culturally bound with children in those cultures first learning the tolerant implication and later learning the intolerant implication.